2018
DOI: 10.1038/s41598-018-25067-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and chronic kidney disease: a cross-sectional association in the Irish Nun Eye Study

Abstract: Associations between dietary patterns and chronic kidney disease are not well established, especially in European populations. We conducted a cross-sectional study of 1033 older Irish women (age range 56–100 years) with a restricted lifestyle. Dietary intake was assessed using a food frequency questionnaire. Renal function was determined by estimated glomerular filtration rate. Two dietary patterns were identified within the study population using factor analysis. A significant negative association was found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…This cross-sectional study revealed that the western dietary pattern, characterized by higher intake of soft drinks, fast food, mayonnaise, cakes, cookies, red meat, sweets, refined grains, salty snacks, French fries, high-fat dairy products, and organ meats, was associated with the increased risk of CKD after adjustment for multiple co-variants in adults with high blood pressure in Iran. In agreement with our findings, several studies have also reported a significant association between adherence to the Western dietary pattern and the risk of kidney function decline (5,(7)(8)(9)(10). In the TLGS, the high fat, high sugar dietary pattern was associated with a 49% increased odds of the incidence of CKD after 6.1 years of follow-up (8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This cross-sectional study revealed that the western dietary pattern, characterized by higher intake of soft drinks, fast food, mayonnaise, cakes, cookies, red meat, sweets, refined grains, salty snacks, French fries, high-fat dairy products, and organ meats, was associated with the increased risk of CKD after adjustment for multiple co-variants in adults with high blood pressure in Iran. In agreement with our findings, several studies have also reported a significant association between adherence to the Western dietary pattern and the risk of kidney function decline (5,(7)(8)(9)(10). In the TLGS, the high fat, high sugar dietary pattern was associated with a 49% increased odds of the incidence of CKD after 6.1 years of follow-up (8).…”
Section: Discussionsupporting
confidence: 91%
“…of the previous studies have been done in East Asia (9,11), Europe (10), and the USA (7,12). Furthermore, to the best of our knowledge, most research to investigate the association between the dietary pattern and renal dysfunction has been conducted in healthy populations (7)(8)(9)(10)12) or diabetics (11) and there is a lack of data on patients with high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory dietary pattern identified in the present study was similar to the Western dietary pattern, characterized by high intakes of meat, processed foods, and sweets but low intakes of fruits and vegetables [27,28]. Our study suggests that inflammatory dietary pattern was associated with an increased risk of dyslipidemia by 21% in males, while females consuming inflammatory dietary pattern only showed a borderline increased risk of dyslipidemia (OR = 1.12, 95% CI: 0.99–1.26, p = 0.052).…”
Section: Discussionmentioning
confidence: 61%
“…For example, a meta-analysis inferred that keeping a healthy diet, such as DASH diet and MD diet, was associated with CKD prevention and decreased the risk of death caused by renal cause at the same time [7]. While an unhealthy diet pattern might lead to increasing the risk of CKD reported by a crosssectional study called Irish Nun and Eye Study [8]. A review about the association between obstructive sleep apnea (OSA) and CKD suggested that sleep-related breathing disorder, such as OSA, indirectly induce CKD by the hypertension, endothelial dysfunction and oxidative [9].…”
Section: Introductionmentioning
confidence: 99%